Long term low emission and climate resilient development strategies - 14 April 2025 - Chevallier, Romy (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This presentation was for the African Group of Negotiators Expert Support (AGNES) Climate Governance, Diplomacy and Negotiations Leadership Program. The Program aims to build and strengthen African climate leaders by improving their knowledge and negotiation skills to enable them to engage effectively in international climate change policy discourse as well as contribute to the successful implementation of climate actions at regional and national levels.